Counterflow Combustion of Micro Organic Particles - Bidabadi, Mehdi; Esmaeilnejad, Ali; Sirousfarshadi, Sirousfarshadi (Journal of Mechanical Engineering and Technology (JMET), 2015)
The structure of counterflow premixed flames in an axisymmetric configuration, containing uniformly distributed volatile fuel particles, with nonunity Lewis number of the fuel are examined. It is presumed that the gaseous fuel, produced from vaporization of the fuel particles, oxidizes in the gas phase and the fuel particles do not participate in the reaction. The analysis is carried out in the asymptotic limit for large values of Zeldovich number.A one-step reaction is assumed. The flame position is determined andthe effect of Lewis number change on fraction distribution is investigated.